Development process improvement of a game development company - Gadi, Peter Paul A. (University of the Philippines Diliman, 2008)
The aim of this project paper is to implement and document process improvement steps undertaken in a game development company. The game development company under study is Anino Games [1], a local game development company of which the author is a shareholder. The author has proposed a DMAIC project to document and improve the game development processes of the said company as the basis of the TM 299.2 paper. Initially, the paper was targeted to merely document the development processes that Anino used that fell under the scope of Agile Game Development [3]. The project has changed during project progress to process improvement. The scope of the paper is to make use of the DMAIC framework, Six Sigma references and Agile Game Development practices in order to ensure that all project deadlines are met. Based on readings on process improvement and the availability of resources, The DMAIC process was chosen as a framework for the project paper. By choosing this framework, the project progressed through several phases of documentation and implementation, at times moving back and forth through the DMAIC phases. At the Define Phase, company documents as well as several game development methodology references were used to understand the company's current processes. Process maps and a SIPOC diagram were created during this phase. Also, the company knowledgebase (which is captured in the company's Trac databases) as well as client contracts were evaluated to determine the Voice of the Customer, to ensure that the proposed project will be attuned to customer needs. Lastly, the Project Charter was created during this phase. At the Measure Phase, data from measurements recorded in the company's internal databases that were related to project delays were extracted. These measurements were then mapped into Pareto Charts and graphs so that they could be visualized more effectively for the next phase.